2020
DOI: 10.47678/cjhe.v50i2.188715
|View full text |Cite
|
Sign up to set email alerts
|

Risk and protective factors for anxiety impacting academic performance in post-secondary students

Abstract: This survey study measured the association between risk and protective factors of anxiety and its implications on the academic performance of 1,053 students at a four-year, public post-secondary institution in southwestern Ontario. Logistic regression analyses revealed 13 significant variables at the univariable level, while the multivariable model yielded seven significant factors. Students who felt hopeless significantly increased their odds of reporting anxiety adversely affecting their academic performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 56 publications
2
17
0
Order By: Relevance
“…There were minor differences among student and on-campus service provider participants' responses, where both groups largely identified the same factors at each socioecological model level. This finding supports the growing literature recognizing the integral role of post-secondary institutions in fostering students' optimal mental wellness and learning [16,38]. Both groups of participants indicated that undergraduate students typically seek services reactively to address their mental health concerns once they are already stressed, indicating a gap in proactive, resilience-focused, upstream efforts at post-secondary institutions to prevent the deleterious effects of stress from initially occurring.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…There were minor differences among student and on-campus service provider participants' responses, where both groups largely identified the same factors at each socioecological model level. This finding supports the growing literature recognizing the integral role of post-secondary institutions in fostering students' optimal mental wellness and learning [16,38]. Both groups of participants indicated that undergraduate students typically seek services reactively to address their mental health concerns once they are already stressed, indicating a gap in proactive, resilience-focused, upstream efforts at post-secondary institutions to prevent the deleterious effects of stress from initially occurring.…”
Section: Discussionsupporting
confidence: 81%
“…Canadian post-secondary institutions are increasingly committed to enhancing students' mental health and academic success through services and programming [16][17][18][19]. However, Linden and Stuart's [20] work argues that there is a limited understanding of the specific evolving sources of stress experienced by Canadian post-secondary students.…”
Section: Introductionmentioning
confidence: 99%
“…Also, an area that could benefit from further research and that is underrepresented within the CJHE is insights into the various psychological and psycho-social factors that affect student success (Lisnyj et al, 2020;Ramey et al, 2018;Wasylkiw et al, 2020). Such studies present a unique and quantitative perspective into the complexities of some predictive factors of student success.…”
Section: Discussion and Directions For Researchmentioning
confidence: 99%
“…Such studies present a unique and quantitative perspective into the complexities of some predictive factors of student success. These authors examined numerous factors that may predict student success, such as perseverance and maternal education (Ramey et al, 2018), contributors to anxiety (Lisnyj et al, 2020), and self-esteem, self-compassion, self-efficacy, and participants' mindsets of their own abilities (Wasylkiw et al, 2020). These studies are all newly published and further studies within the field of the predictive validity of psychological outcomes in academic success would likely be a welcome addition to the student success literature within the CJHE and the broader field of higher education.…”
Section: Discussion and Directions For Researchmentioning
confidence: 99%
See 1 more Smart Citation